Silent myocardial ischaemia in patients with proved coronary artery disease: a comparison of diabetic and non-diabetic patients. Issue 908 (1st June 2001) - Ditchburn, C J; Hall, J A; de Belder, M; Davies, A; Kelly, W; Bilous, R
Abstract : OBJECTIVE: To determine whether diabetic patients with coronary artery disease are more likely to experience silent myocardial ischaemia than subjects without diabetes. SUBJECTS: Patients undergoing coronary angiography at a regional cardiothoracic unit, identified as having diabetes from the local district diabetic register/database. DESIGN: The coronary angiograms and exercise treadmill tests of 100 diabetic and 100 non-diabetic patients who all had significant coronary artery disease and maximal effort exercise tests were reviewed. Patients were individually matched for age group, gender, severity of coronary artery disease, and indication for treadmill test. OUTCOME MEASURES: Significant coronary artery disease was defined as a stenosis of greater than 50% diameter in at least one of the major coronary artery segments. Exercise tests were graded as positive if the electrocardiographic (ECG) recording showed planar or downsloping ST segment depression of ⩾1 mm in more than two leads at 80 ms post J-point or if there was a blood pressure fall ⩾10 mm Hg after an initial rise. A negative exercise test was defined as one in which the subject experienced no pain, had no ECG changes after maximal effort and had a normal blood pressure response. Subjects who did not experience any form of typical angina-type pain during a positive exercise test were defined as having an episode of silent ischaemia. Patients with symptomatic ischaemia were those who experienced typical angina-type pain with accompanying ST segment changes. Patients with a negative exercise test were defined as having "undetermined ischaemia". This category included all those without ECG evidence of myocardial ischaemia during the exercise test (with or without accompanying chest pain). RESULTS: In the diabetic patients, 34% had ECG evidence of silent ischaemia on treadmill testing compared with only 19% of the non-diabetic controls (p<0.02). CONCLUSIONS: This study shows that diabetic patients with proved coronary artery disease have a higher risk of developing silent myocardial ischaemia during exercise than non-diabetic patients.